IgT and IgD dominance in the teleost central nervous system - Vicente-Gil, Samuel; Pianese, Valeria; Morel, Esther; Abós, Beatriz; Jiménez-Barrios, Pablo; Perdiguero, Pedro; Martín, Diana; Simón, Rocío; Picchietti, Simona; Scapigliati, Giuseppe; Tafalla, Carolina (Frontiers in Immunology, 2025)
Although initially described as an immune-privileged site, the central nervous system (CNS) is now known to harbor a resident immune system, composed of different innate and adaptive cell types that maintain tissue homeostasis, are regulated in pathological conditions or brain injury and are in connection with the peripheral immune system. However, information regarding a characterization of the B cell subsets colonizing the CNS or their precise role is very scarce in mammals and even more in fish. Teleost fish exclusively express IgM, IgD and the teleost-specific IgT and their expression patterns in B cells define diverse B cell subsets. IgM is the main Ig isotype in systemic responses, while previous evidence suggested a mucosally dedicated role for IgT. Recent work by our group and others, also pointed to a role for IgD in maintaining mucosal homeostasis. However, in the current study, we demonstrate through different techniques that IgD+ and IgT+ expressing B cells are predominant in the teleost CNS, albeit a very different distribution. Additionally, B cell receptor (BCR) repertoire analysis pointed to both populations as antigen-experienced. Further research is needed to fully elucidate the specific roles of IgT and IgD in the teleost brain, but this discovery opens exciting avenues for future investigations in the fields of immunology and neuroscience.